Analysis of serpentinophytes from north-east of Portugal for trace metal accumulation--relevance to the management of mine environment. - Freitas, H.; Prasad, M. N. V.; Pratas, J. (Chemosphere, 2004)
In north-east of Portugal, the serpentinized area is about 8000 ha with a characteristic geology and flora. The serpentine plant community and respective soils were analyzed to examine the trace metal budget in different tissues of the plants exhibiting resistance to trace metals. One hundred and thirty five plant species belonging to 39 families and respective soils have been analyzed for total Co, Cr, Cu, Fe, Mn, Ni, Pb and Zn. Substantial amounts of Ni, Cr, Co and Mn were detected in plant tissues which are listed below: NI: Alyssum serpyllifolium (38105); Bromus hordeaceus (1467); Linaria spartea (492); Plantago radicata (140); Lavandula stoechas (118) and Cistus salvifolius (114); CR: L. spartea (706.7); Ulmus procera (173.4); A. serpyllifolium (129.3); Cistus ladanifer (40.8); L. stoechas (29.5); P. radicata (27.81); Setariopsis verticillata (25.7); Plantago lanceolata (24); Digitalis purpurea (23.4); Logfia minima (23.1); Arenaria querioides (23); Hieracium peleteranum (22.7); Arenaria montana (14.5); CO: A. serpyllifolium (145.1); L. spartea (63.2); P. radicata (10.4); H. peleteranum (7.3); Lepidium heterophyllum (6.9); A. querioides (6.6); C. salvifolius (6.5); C. ladanifer (6.3); L. stoechas (6.1); Anthyllis lotoides (6.1); L. minima (6.1); Euphorbia falcata (5.7) and B. hordeaceus (5.6); MN: A. serpyllifolium (830); L. spartea (339); L. stoechas (187.1); L. minima (182.7); Castanea sativa (125); Spergula pentandra (124); P. radicata (119); Cytisus striatus (115.4); Quercus pyrenaica (110); Teucrium scorodonia (109.4); Fraxinus vulgaris (109); Anthyllis sampaiana (108); Quercus ilex (108). The significance of serpentine flora, need for conservation of these fragile and environmentally invaluable plant resources for possible use for in situ remediation of metalliferous substrates are presented in this paper.
The following values have no corresponding Zotero field: accession-num: 14675842
Keywords: Environmental significance; Metal accumulators; Phytodiversity; Remediation; Serpentinophytes